STANDARDIZATION OF CELERY LEAVES PREPARATION (Apium graveolens L.) BY THIN LAYER CHROMATOGRAPHIC – DENSITOMETRY USING APIGENIN AS PARAMETER - Djatmiko M.; Pramono S. (Faculty of Pharmacy Universitas Gadjah Mada, Yogyakarta, Skip Utara, 55281, Indonesia, 2001)
In order to apply a standardization method on herbal medicines or pharmaceuticals, a thin layer chromatographic-densitometry was used to determine apigenin as the active constituent of celery extract formulated in a capsule dosage form. Silica gel GF 254 and chloroform – methanol – water (70 – 30 – 6,5 v/v) were used as stationary and mobile phases, respectively. The areas of apigenin were evaluated at 340 mm using a TLC-Scanner.The limit of detetion was 3 g and the accuracy was 89,6% after first extraction prosedure applied on celery capsules. The apigenin content was 0,017 %.Key Words : Apium graveolens L., apigenin, TLC – densitometry.